Preparation and Characterization of Ink from Hibiscus sabdariffa, Curcuma longa and Sorghum vulgare - Idara U. Ntuen; Aniekan Effiong Akpakpan; Godwin Enin; Iniobong Sylvester Enengedi; Emaime Jimmy Uwantta; Edet William Nsi; Itoro E. Udo; Edidiong Emmanuel Ikpe; Ukana Davies Akpabio (Nepal Journal of Biotechnology)
Hibiscus sabdariffa (Roselle flower), Curcuma longa (Turmeric) and Sorghum vulgare (Guinea corn) are utilised in Nigeria for food and as natural colorants in home industries for dye and beverage production. The study investigates the formulation, characterization, and production of inks from these plant extracts using standard procedures. Inks were prepared from water-based and methanol-based extracts of Turmeric (WTE and MTE), Guinea corn stalk (WGE and MGE), and Roselle flower (WRE and MRE), with Dacryodes edulis exudate serving as a binder of eco-friendly, sustainable and cost-effective stamp pad ink. The raw materials were characterized according to standard procedures. Different ratios of the plant extracts were used to formulate the inks, with the optimal blend selected for stamp pad production. Characterization of the inks were conducted using Fourier Transform Infrared spectrometer (FTIR), Ultra violet/visible (UV/vis) spectrometer, viscometer and pH meter. Results indicated the presence of phytochemicals such as alkaloids, tannins, saponins and flavonoids. The inks exhibited viscosity ranging from 121.06 –313.86 kgm-1s-1, absorbance values from 0.010 – 2.578, and pH levels from 3.1- 6.5. FTIR analysis showed the inks contain chromophores and auxochromes including NO, C=C, C=O, C≡C, and -OH groups. Drying times for the formulated inks varied from 3 –11 minutes, compared to 1-3 minutes for the control ink, with methanol-based formulated inks (MbFI) drying faster than water-based formulated ink (WbFI). The produced stamp pad demonstrated good ink adhesion on paper.